Expression and clinical significance of IL-6 in patients with allergic rhinitis - Maqsood, Reshaib; Iqbal, Hanan; Gul, Samreen; Ali, Ihsan; Malik, Junaid (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Allergic rhinitis is a chronic inflammatory disease with a high incidence affecting the quality of life of patients. The objective of the study was to explore the expression and clinical significance of IL-6 in patients with allergic rhinitis. Methods: This cross-sectional analytical study was conducted in the department of ENT, H&NS, Government Medical College, Srinagar. A total of 180 patients were included in the study, out of them 90 patients with allergic rhinitis were cases and 90 patients comprised the control group who did not have allergic rhinitis. The recorded data was compiled and entered in a spreadsheet (Microsoft Excel) and then exported to data editor of SPSS Version 20.0 (SPSS Inc., Chicago, Illinois, USA). Results: A total of 184 patients participated in the study. The mean age in case group was 35.7±15.46 years compared to control group which was 37.1±12.89 years. There was male dominance in both the groups. Comparison of IL-6 levels as per severity of allergic rhinitis was assessed in this study and it was found that in patients with severe allergic rhinitis the mean IL-6 levels were 65.2±5.32; in moderate, patients had IL-6 levels of 52.8±5.84 and in mild patients had IL-6 levels of 46.7±6.81. Conclusions: Clinical testing of IL-6 is likely to improve the diagnostic rate of early allergic rhinitis and help in halting the progression of disease and improve the patients prognosis and reduce symptoms and morbidity. Higher the levels of IL_6 more severe will be the allergic rhinitis.